2012
DOI: 10.1583/jevt-12-3942c.1
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Drug-Eluting Balloons for Carotid In-Stent Restenosis: Can This Technology Deliver the Goods?

Abstract: Percutaneous transluminal treatment of coronary and peripheral artery diseases has revolutionized the field of interventional medicine. Over the years, progressive technological and pharmacological advances have improved clinical outcome and offered an effective alternative to surgical treatment of atherosclerotic disease in both coronary and peripheral districts. Relatively new to this field are drug-eluting balloons (DEBs), which represent an attractive and novel treatment modality that offers numerous theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 25 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…DEB can circumnavigate the limitations of stent placement, while concurrently releasing an antiproliferative agent to minimize neointimal hyperplasia. Unlike the drug‐eluting stent in which the drug is slowly released from a polymer coating, the DEB is freely coated with drug, avoiding the need for a polymer, which leads to more rapid vascular healing 13,28 . DEBs consist of a balloon catheter, a lipophilic antiproliferative drug, and a drug carrier (excipient) that increases the solubility of the drug 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEB can circumnavigate the limitations of stent placement, while concurrently releasing an antiproliferative agent to minimize neointimal hyperplasia. Unlike the drug‐eluting stent in which the drug is slowly released from a polymer coating, the DEB is freely coated with drug, avoiding the need for a polymer, which leads to more rapid vascular healing 13,28 . DEBs consist of a balloon catheter, a lipophilic antiproliferative drug, and a drug carrier (excipient) that increases the solubility of the drug 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It is highly lipophilic, allowing a unique duality of longer retention in vascular smooth muscle and therefore longer antiproliferative action and a lower systemic toxicity, making it an ideal drug for use in the DEB 13 . The IN.PACT™ Admiral™ (Medtronic) DEBs that were used in our 2 patients contain 3.5 μg/mm 2 of paclitaxel with urea as the excipient, which has been considered a better alternative to older excipients such as contrast, as they are associated with cases of delayed intimal healing and inflammation 28 . Although an inflation time of 180 seconds is strongly recommended, as per the manufacturer, adequate drug transfer occurs in the first 60 seconds of inflation, with studies showing that even a short exposure to the drug causes sustainable modifications in the cytoskeletal structure 29 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous reports have indicated that repeated stent placement, angioplasty with balloon techniques, and surgical treatments are the main treatments for ISR. Recently, drug-coated balloons (DCBs) or drug-eluting balloons (DEBs), with the features of homogenous distribution of antiproliferative drugs to the vessel wall, 10 have been advocated for treatment of ISR in the coronary and femoropopliteal areas in recent years, but an overview of this application in the carotid artery restenosis is still lacking. 11,12 It has been reported that DCB angioplasty showed satisfactory efficacy in carotid artery stenosis and in-stent restenosis in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, when the lesion was not suitable for Precise implantation (e.g. in case of in-stent restenosis or when the reference vessel diameter was too large), we used balloon-only angioplasty or employed other types of stents [8][9] . All devices were used according to their instructions for use, unless in bailout conditions.…”
Section: Methodsmentioning
confidence: 99%